1993
DOI: 10.1289/ehp.93101s4205
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to working group on tropospheric ozone, Health Effects Institute environmental epidemiology planning project.

Abstract: The working group on tropospheric ozone of the Health Effects Institute has evaluated the need for epidemiologic studies on the health effects of ozone (03) exposure. This paper summarizes current data and identifies possible research questions. The extent to which ozone exposure results in chronic health effects is largely undefined and is the central issue for epidemiologic studies. Most current data focus on transient endpoints; the link between acute changes in symptoms and/or lung function and possible ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…An increase in atmospheric CO concentrations could reduce the self‐cleansing ability of the atmosphere and thus modify its chemical, physical, and climatological properties. In the presence of nitrogen oxides, it is a precursor to the formation of tropospheric ozone [ Ridley et al , 1992], which in turn leads to crop damage and human health problems through its effect on the respiratory system [ Tager , 1993].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in atmospheric CO concentrations could reduce the self‐cleansing ability of the atmosphere and thus modify its chemical, physical, and climatological properties. In the presence of nitrogen oxides, it is a precursor to the formation of tropospheric ozone [ Ridley et al , 1992], which in turn leads to crop damage and human health problems through its effect on the respiratory system [ Tager , 1993].…”
Section: Introductionmentioning
confidence: 99%
“…trations is a major remaining uncertainty regarding ozone health effects (7). However, the public health significance of these short-term reversible effects remains uncertain.…”
mentioning
confidence: 99%
“…Long-term animal studies have observed morphological changes consistent with early stages of fibrosis at the bronchiolar/alveolar junction in the deep lung-changes that mimic those observed in autopsies of young cigarette smokers (4-6). Whether similar changes occur in humans exposed repeatedly over long periods to ambient ozone concentrations is a major remaining uncertainty regarding ozone health effects (7).…”
mentioning
confidence: 99%